Heat transfer fin loaded with adsorbent particles, adsorption type heat exchange module provided with heat transfer fin, and manufacturing methods of heat transfer fin and adsorption type heat exchange module
By forming an adsorbent layer with a specific structure on the heat transfer fins of the adsorbent heat transfer assembly, the problem of easy peeling of the adsorbent layer and shrinking the interval of the heat transfer fins during the mechanical processing is solved, and efficient latent heat treatment and a compact dehumidification system are achieved.
Patent Information
- Application Number
- CN202380066546.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-20
- Filing Date
- 2023-12-26
- Publication Date
- 2025-04-25
AI Technical Summary
In the existing adsorption heat exchange module, the adsorbent layer is easily peeled off during mechanical processing, and the heat transfer fins are easily blocked when the intervals are reduced, resulting in low heat exchange efficiency.
A metal plate with excellent thermal conductivity is used as a base material, and a corrosion-resistant film containing an epoxy resin is applied on it, and adsorbent particles formed of organic polymers having a specific carboxyl group amount and an adsorbent layer composed of polyamines, reactive diluents having two or more epoxy groups, and a binder formed of an epoxy resin.
The high strength and adhesion of the adsorbent layer are achieved, the peeling of the adsorbent layer during mechanical processing is avoided, and the interval between heat transfer fins can be reduced, the adsorbent amount per unit volume can be increased, and the latent heat treatment efficiency can be improved.
Smart Images

Figure CN119895221A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a heat transfer fin loaded with adsorbent particles, an adsorption heat exchange component with the heat transfer fin and a manufacturing method thereof. Background Art
[0002] In recent years, adsorption heat exchangers have attracted much attention as heat exchangers for air conditioners. Adsorption heat exchangers use the endothermic / exothermic reaction generated by the desorption / adsorption of adsorbed substances on the adsorbent to exchange temperature and humidity between exhaust and intake air during ventilation, which can reduce the air conditioning energy loss generated during ventilation in the past.
[0003] For example, in the sorption reactor assembly reported in Patent Document 1, fins loaded with inorganic sorbents such as silica gel and zeolite are disclosed. However, inorganic sorbents have many problems, such as low moisture absorption, high temperature required for regeneration of the sorbent, embrittlement of the sorbent and powder shedding caused by repeated moisture absorption and desorption, etc.
[0004] Therefore, in the fins of the adsorption heat exchange component described in Patent Document 2, an organic polymer adsorbent is used. The organic polymer adsorbent can absorb more water than an inorganic adsorbent and will not become brittle even if it absorbs and releases moisture repeatedly. However, since the organic polymer adsorbent has the property of swelling / contracting when absorbing / releasing moisture, in the existing method of applying a coating liquid mixed with an adsorbent and a solvent to a substrate and drying to form an adsorbent layer, when water is used as a solvent, there is a problem of cracking of the adsorbent layer due to the volume change that occurs during the formation of the adsorbent layer. In addition, the adhesion with the substrate is also poor, and the adsorbent layer will fall off under conditions such as immersion in water, which is also a problem with existing polymer adsorbents.
[0005] In addition, the heat exchange component as described above is composed of plate fins loaded with adsorbent and heat transfer tubes with heat medium flowing inside. The more the plate fins are, the larger the adsorbent layer area and adsorbent amount per unit volume of the heat exchange component are, and the heat exchange capacity can be improved. However, the heat exchange component as described above is manufactured by immersing the assembled component in a coating liquid containing adsorbent. Therefore, if the number of heat transfer fins is increased and the interval between the heat transfer fins is reduced, the drainage after immersion will be insufficient, and even after drying, the gap between the heat transfer fins will be in a state of being blocked by the adsorbent and become easily blocked. Therefore, there is a limit to increasing the number of heat transfer fins.
[0006] In this regard, if the adsorbent is loaded onto the heat transfer fins before the assembly of the module, the problem of poor drainage after impregnation can be avoided. However, for the heat transfer fins loaded with the adsorbent layer, the adsorbent layer may crack or peel off during the punching process for inserting the heat transfer tube and the module assembly process, so it is difficult to obtain a practical adsorption heat exchange module.
[0007] Regarding the suppression of cracking and peeling of the adsorbent layer, Patent Document 3 discloses a countermeasure, namely, applying a corrosion-resistant film on the surface of the heat transfer fins and bonding the corrosion-resistant film to the adsorbent with an adhesive. However, the above countermeasure can only cope with the volume change accompanying moisture absorption and release, and is not sufficient to withstand processing such as punching. Although it is also considered to improve the suppression effect of cracking and peeling by increasing the amount of adhesive, the moisture absorption performance is difficult to fully exert due to the increased coverage of the adhesive on the adsorbent, and therefore the latent heat treatment efficiency will be reduced.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 6-2984
[0011] Patent Document 2: Japanese Patent Application Publication No. 2006-200850
[0012] Patent Document 3: Japanese Patent Application Publication No. 2012-77987 Summary of the invention
[0013] Problem that the invention aims to solve
[0014] The present invention is created in view of the current status of the above-mentioned prior art, and its purpose is to provide a heat transfer fin having an adsorbent layer that is not easy to peel off and has strength that can withstand mechanical processing and a high moisture absorption and desorption capacity. In addition, a further purpose of the present invention is to provide an adsorption heat exchange component with excellent latent heat treatment efficiency, which, by using the heat transfer fin, can be punched and assembled after the adsorbent layer is loaded, thereby reducing the heat transfer fin interval and increasing the adsorbent amount per unit volume of the component.
[0015] Solutions for solving problems
[0016] The inventors of the present invention have conducted intensive research to achieve the above-mentioned purpose, and as a result, have found that the above-mentioned purpose can be achieved by using the following heat transfer fins, thereby completing the present invention. The heat transfer fins include: a corrosion-resistant film containing epoxy resin on the surface of a metal plate with excellent thermal conductivity; an adsorbent layer containing adsorbent particles formed by an organic polymer having a specific amount of carboxyl groups and a binder formed by polyamine, a reactive diluent having two or more epoxy groups and an epoxy resin.
[0017] That is, the present invention is achieved by the following means.
[0018] [1] A heat transfer fin characterized by comprising: a corrosion-resistant film provided on the surface of a metal plate having excellent thermal conductivity and containing an epoxy resin; an adsorbent layer containing adsorbent particles formed of an organic polymer having a carboxyl group and a binder formed of a polyamine, a reactive diluent having two or more epoxy groups, and an epoxy resin; the organic polymer has a carboxyl group content of 3 to 10 mmol / g and a neutralization degree of 60 to 100%, 30 to 110 parts by weight of the binder is used with respect to 100 parts by weight of the adsorbent particles, and the adsorbent particles and the binder are used in a total of 20 to 80 g / m 2 The amount is loaded on one side of the surface of the aforementioned metal plate.
[0019] [2] The heat transfer fin according to [1], wherein the viscosity of the reactive diluent at 25° C. is 500 mPa·s or less.
[0020] [3] The heat transfer fin according to [1], characterized in that the epoxy equivalent of the reactive diluent is 50 to 200 g / eq.
[0021] [4] The heat transfer fin according to [1], wherein the weight average particle size of the adsorbent particles is 3 to 100 μm.
[0022] [5] The heat transfer fin according to [1], characterized in that the swelling ratio of the adsorbent particles in water is 5 times or less.
[0023] [6] A method for manufacturing a heat transfer fin as described in any one of [1] to [5], characterized in that it includes the following steps: applying a coating liquid on the surface of a metal plate to which a corrosion-resistant film containing an epoxy resin is applied and baking the coating liquid, wherein the coating liquid contains adsorbent particles formed by an organic polymer having a carboxyl group, a polyamine, a reactive diluent having two or more epoxy groups, an epoxy resin and an organic solvent.
[0024] [7] The method for producing a heat transfer fin according to [6], characterized in that a ketone is used as the organic solvent.
[0025] [8] The method for manufacturing a heat transfer fin according to [6] is characterized in that it includes the following steps: adding polyamine to a solution containing epoxy resin, a reactive diluent having two or more epoxy groups, an organic solvent, and adsorbent particles formed by an organic polymer having a carboxyl group to prepare a coating liquid.
[0026] [9] An adsorption heat exchange component, characterized in that it is composed of a plurality of heat transfer fins provided with an adsorbent layer and a heat transfer tube penetrating the plurality of heat transfer fins.
[0027] The plurality of heat transfer fins are the heat transfer fins described in [1], and there is no blocking portion caused by the adsorbent layer between adjacent heat transfer fins.
[0028]
[10] The adsorption heat exchange component according to [9] is characterized in that the interval between adjacent heat transfer fins is less than 2 mm.
[0029]
[11] The adsorption heat exchange component according to [9] is characterized in that the amount of adsorbent per unit volume is 20 to 60 kg / m 3 .
[0030]
[12] A method for manufacturing an adsorption heat exchange component according to any one of [9] to
[11] , characterized in that it comprises the following steps:
[0031] The step of providing an adsorbent layer on the surface of the heat transfer fin provided with the corrosion-resistant film, wherein the adsorbent layer contains adsorbent particles formed of an organic polymer having a carboxyl group in the molecule and a binder formed of a polyamine, a reactive diluent having two or more epoxy groups and an epoxy resin;
[0032] A step of punching holes in the heat transfer fins provided with the adsorbent layer to form holes; and
[0033] The step of inserting the heat transfer tube into the aforementioned plurality of holes.
[0034]
[13] A dehumidification system using the adsorption heat exchange component described in any one of [9] to
[11] .
[0035]
[14] A ventilation and air-conditioning system using the adsorption heat exchange element described in any one of [9] to
[11] .
[0036] Effects of the Invention
[0037] The heat transfer fins of the present invention not only have excellent moisture absorption performance, durability and water resistance, but also can load adsorbents by online coating on metal plates when manufacturing heat exchange components. Therefore, compared with the existing method of repeatedly immersing in a coating liquid containing adsorbents and drying after assembly of the components, the production speed is greatly improved, and the uniformity of the adsorbent loading amount is also improved. In addition, the adsorption type heat exchange component of the present invention manufactured using the above-mentioned heat transfer fins can reduce the interval between the heat transfer fins, thereby increasing the amount of adsorbent per unit volume of the component, so that a heat exchange component that is more compact and has excellent latent heat treatment efficiency can be made than before. Since the above-mentioned adsorption type heat exchange component of the present invention can construct a compact and efficient dehumidification system, it can be applied to dehumidification systems such as latent heat and sensible heat separation air conditioners and frost-free refrigeration equipment that can suppress frost during low-temperature operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a diagram showing a typical example of the adsorption heat exchange element of the present invention.
[0039] Figure 2 Graph showing the temporal changes in the cumulative moisture absorption of the adsorption heat exchange components of Example 11, Example 21 and Comparative Example 11. DETAILED DESCRIPTION
[0040] The heat transfer fin of the present invention comprises: (1) a metal plate having excellent thermal conductivity, (2) a corrosion-resistant film provided on the metal surface, and (3) an adsorbent layer containing adsorbent particles and a binder. Each element is described below.
[0041] (1) Metal plates with excellent thermal conductivity
[0042] The metal plate with excellent thermal conductivity in the present invention (hereinafter also referred to as the substrate) is equivalent to the substrate part of the heat transfer fin. As the type of metal used, silver, copper, gold, aluminum, steel, etc. can be cited as examples, but when the thermal conductivity is 50 (W / m·K) or more, efficient heat exchange can be performed, so it is preferred. Among them, from the perspective of price, aluminum, aluminum alloy, copper, and copper alloy are more preferred in practical use. In addition, there is no particular limitation on the shape of the substrate, and a flat plate, corrugated, corrugated, partially open-hole shape, etc. can be appropriately selected according to the purpose.
[0043] In addition, the thickness of the substrate (hereinafter also referred to as the plate thickness) is preferably 0.03 to 1.0 mm, more preferably 0.04 to 0.6 mm, and further preferably 0.05 to 0.4 mm. If the plate thickness is less than 0.03 mm, it is easy to break, break, deform, etc. due to external forces, so there is a concern that it will be difficult to operate in each process of processing into a heat exchange component. In addition, if the plate thickness exceeds 1.0 mm, it is difficult to transfer the heat of the heat transfer tube to the adsorbent layer, so there is a concern that sufficient performance cannot be obtained.
[0044] (2) Corrosion-resistant film
[0045] The corrosion-resistant film in the present invention is provided on the surface of the substrate for the purpose of preventing corrosion of the substrate and improving the adhesion between the adsorbent layer and the substrate. The primer component used to form the above-mentioned corrosion-resistant film is an epoxy resin with good adhesion to the substrate and the adsorbent layer, among which acrylic modified epoxy resin is preferred. In addition, when the substrate is an aluminum-based material, a base treatment such as phosphochromate treatment is usually performed first, and then the above-mentioned primer component is applied to form the corrosion-resistant film.
[0046] (3) Adsorbent layer
[0047] The adsorbent layer in the present invention is mainly composed of adsorbent particles and a binder (hereinafter also referred to as a binder) composed of a reactive diluent having two or more epoxy groups, a polyamine, and an epoxy resin.
[0048] (3-1) Adsorbent particles
[0049] The adsorbent particles are composed of an organic polymer having a carboxyl group. Since the carboxyl group has the property of reversibly adsorbing water vapor in the air, the adsorbent particles formed by the organic polymer have moisture absorption and desorption capabilities. The lower limit of the total amount of carboxyl groups contained in the organic polymer is 3 mmol / g, preferably 4 mmol / g. When the amount of carboxyl groups is less than 3 mmol / g, the moisture absorption and desorption required by the present invention cannot be fully obtained. In addition, the upper limit is 10 mmol / g, preferably 7 mmol / g. When the amount of carboxyl groups exceeds 10 mmol / g, the adsorbent particles absorb moisture excessively and swell, resulting in impaired water resistance.
[0050] In addition, in order to improve the hygroscopic performance, at least a part of the aforementioned carboxyl groups is neutralized. At this time, the cations that form a pair therewith can be, for example, alkali metals such as Li, Na, K, Rb, Cs, alkaline earth metals such as Mg, Ca, Sr, Ba, organic cations such as NH4, amines, etc. From the viewpoint of moisture absorption and release rate, alkali metal and alkaline earth metal cations are preferred, and sodium and potassium are more preferred. At this time, the ratio of the counter ions in all carboxyl groups to the aforementioned cations, i.e., the degree of neutralization, has a lower limit of 60%, preferably 65%. If the degree of neutralization is lower than 60%, the aforementioned adsorbent particles cannot obtain sufficient hygroscopic performance. In addition, although there is no particular upper limit, according to the definition of the above-mentioned degree of neutralization, the degree of neutralization will not exceed 100%.
[0051] The lower limit of the weight average particle size of the adsorbent particles is preferably 3 μm, more preferably 10 μm, and further preferably 20 μm. When the weight average particle size is less than 3 μm, the particles will be buried in the binder and will not be able to fully exert their hygroscopic properties. In addition, as an upper limit, it is preferably 100 μm, and more preferably 50 μm. When the weight average particle size exceeds 100 μm, the film-forming property is reduced, resulting in cracking and peeling of the coating film, which is not preferred.
[0052] The swelling ratio of the adsorbent particles in water is preferably 5 times or less, more preferably 3 times or less. If the swelling ratio in water exceeds 5 times, the adsorbent layer containing the adsorbent particles is easily peeled off from the substrate, which is not preferred.
[0053] The above-mentioned adsorbent particles can be manufactured by an existing method of polymerizing monomers to form polymers. At this time, there is no particular limitation on the monomers, and vinyl monomers can be appropriately selected as a representative. In addition, there is no particular limitation on which method to use, for example, the following methods can be cited: a method of obtaining a polymer by homopolymerizing a monomer having a salt-type carboxyl group or copolymerizing it with other copolymerizable monomers (the first method); a method of first obtaining a polymer having a carboxyl group and then converting it into a salt form (the second method); a method of polymerizing a monomer having a functional group that can be derived into a carboxyl group, converting the functional group of the obtained polymer into a carboxyl group through chemical modification, and then converting it into a salt form (the third method); or a method of implementing the above three methods by graft polymerization; etc.
[0054] As a method for polymerizing monomers having salt-type carboxyl groups in the above-mentioned first method, for example, the following methods can be cited: polymerizing salt-type monomers corresponding to monomers containing carboxyl groups such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, vinyl propionic acid, etc. alone; or polymerizing two or more of these monomers; or polymerizing a mixture of the same monomer but in carboxylic acid form and in corresponding salt form; in addition, these monomers can also be copolymerized with other copolymerizable monomers; etc.
[0055] In addition, the method that the second method is described in obtaining having carboxyl polymkeric substance and is changed into salt type for example refers to the following method: first obtain the homopolymer of the acidic monomer that contains carboxyl as described above by polymerization or the multipolymer formed by more than 2 kinds of this monomer or the multipolymer of other monomers that can copolymerize, and then be changed into salt type.As the method that carboxyl is converted into salt type, it is not particularly limited, can be by making the aforementioned acidic polymkeric substance that obtains and comprise the solution of organic cations such as alkaline earth metal ions, NH4, amine such as alkali metal ions such as Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, carry out methods such as ion exchange and realize conversion.
[0056] As a method of introducing a carboxyl group by chemical modification in the third method, for example, there is the following method: first polymerize a homopolymer of a monomer having a functional group that can be modified to a carboxyl group by chemical modification, or a copolymer formed by two or more of the monomers, or a copolymer with other copolymerizable monomers, and then modify the obtained polymer to a carboxyl group by hydrolysis. In the case where the obtained state is not a salt form, the above-mentioned method of converting the modified carboxyl group into a salt form is adopted. As monomers that can be used in this method, monomers having a nitrile group such as acrylonitrile and methacrylonitrile; anhydrides, ester derivatives, amide derivatives, and cross-linking ester derivatives of monomers having a carboxylic acid group such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, and vinyl propionic acid can be cited.
[0057] Examples of the anhydride of the monomer having a carboxylic acid group include maleic anhydride, acrylic anhydride, methacrylic anhydride, itaconic anhydride, phthalic anhydride, N-phenylmaleimide, and N-cyclomaleimide.
[0058] Examples of the ester derivatives of the monomer having a carboxylic acid group include alkyl ester derivatives of methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, lauryl, pentadecyl, hexadecyl, stearyl, behenyl, 2-ethylhexyl, isodecyl, and isopentyl groups; alkyl ether ester derivatives of methoxyethylene glycol, ethoxyethylene glycol, methoxypolyethylene glycol, ethoxypolyethylene glycol, polyethylene glycol, methoxypropylene glycol, propylene glycol, methoxypolypropylene glycol, polypropylene glycol, methoxypolytetraethylene glycol, polytetraethylene glycol, polyethylene glycol-polypropylene glycol, polyethylene glycol-polytetraethylene glycol, polypropylene glycol-polytetraethylene glycol, and butoxyethyl groups; alkyl ether ester derivatives of cyclohexyl, Cyclic compound ester derivatives such as tetrahydrofurfuryl, benzyl, phenoxyethyl, phenoxypolyethylene glycol, isobornyl, neopentyl glycol benzoate, etc.; hydroxyalkyl ester derivatives such as hydroxyethyl, hydroxypropyl, hydroxybutyl, hydroxyphenoxypropyl, hydroxypropylphthaloylethyl, chlorohydroxypropyl, etc.; aminoalkyl ester derivatives such as dimethylaminoethyl, diethylaminoethyl, trimethylaminoethyl, etc.; carboxylic acid alkyl ester derivatives such as (meth)acryloyloxyethyl succinate and (meth)acryloyloxyethyl hexahydrophthalate; alkyl ester derivatives containing a phosphate group or a phosphate ester group such as (meth)acryloyloxyethyl acid phosphate and (meth)acryloyloxyethyl acid phosphate;
[0059] Ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,6-hexanediol (meth)acrylate, 1,9-nonanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, glycerol dimethacrylate, 2-hydroxy-3-acryloxypropyl Crosslinkable alkyl esters such as (meth)acrylate, ethylene oxide adduct di(meth)acrylate of bisphenol A, propylene oxide adduct di(meth)acrylate of bisphenol A, neopentyl glycol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, dihydroxymethyltricyclodecane di(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate; fluorinated alkyl ester derivatives such as trifluoroethyl, tetrafluoropropyl, hexafluorobutyl, and perfluorooctylethyl.
[0060] Examples of amide derivatives of monomers having a carboxylic acid group include amide compounds such as (meth)acrylamide, dimethyl(meth)acrylamide, monoethyl(meth)acrylamide, and n-tert-butyl(meth)acrylamide. Other methods for introducing a carboxyl group by chemical modification include oxidation of olefins, alkyl halides, alcohols, aldehydes, and the like.
[0061] There is no particular limitation on the method of introducing salt-type carboxyl groups by hydrolysis of the polymer in the third method, and known hydrolysis conditions can be used. For example, the following methods can be cited: a method of introducing salt-type carboxyl groups into a polymer obtained by polymerizing and cross-linking the above-mentioned monomers using an alkaline aqueous solution of an alkali metal hydroxide, such as sodium hydroxide, lithium hydroxide, potassium hydroxide or ammonia; or a method of reacting with an inorganic acid such as nitric acid, sulfuric acid, hydrochloric acid or an organic acid such as formic acid or acetic acid to first form a carboxylic acid group, and then mixing with an alkali metal salt to introduce a salt-type carboxyl group by ion exchange. Among them, the hydrolysis method using potassium hydroxide, which can simply obtain potassium salt-type carboxyl groups with excellent moisture absorption rate, is preferred. It should be noted that for conditions reaching 3 to 10 mmol / g, the relationship between reaction factors such as reaction temperature, concentration, and time and the amount of salt-type carboxyl groups introduced can be determined by experiments to clarify.
[0062] In addition, the adsorbent particles used in the present invention preferably have a cross-linked structure. This cross-linked structure can reduce the swelling of the particles caused by moisture absorption or water absorption. As the above-mentioned cross-linked structure, there is no special limitation as long as it does not undergo physical and chemical modification due to moisture absorption and moisture release, and it can be any structure such as cross-linking formed by covalent bonds, ionic cross-linking, cross-linking formed by interaction between polymer molecules or crystal structure. In addition, the method of introducing cross-linking is not particularly limited, and the following methods can be cited: in each of the above-mentioned first method, second method, and third method, in the polymerization stage of the monomer, a method of introducing cross-linking by copolymerizing a cross-linking monomer; or, first polymerizing the above-mentioned monomer, and then introducing a cross-linked structure by chemical reaction or using physical energy, that is, a post-cross-linking method. Among them, the method of using a cross-linking monomer in the polymerization stage of the monomer, or the method of chemical post-cross-linking after obtaining the polymer, can introduce a strong cross-linking based on a covalent bond, which is particularly preferred from the perspective of not being easily physically and chemically modified by moisture absorption and moisture release.
[0063] In the method of using a crosslinking monomer in the polymerization stage of the monomer, especially in the case of an organic polymer adsorbent having a salt-type carboxyl group, a crosslinking monomer that can be copolymerized with the above-mentioned monomer having a carboxyl group or a monomer that can be modified to a carboxyl group is used, and a crosslinked polymer having a crosslinking structure based on a covalent bond can be obtained by copolymerization. However, in this case, it is necessary to use a crosslinking monomer that does not or is unlikely to be affected by the acidic conditions embodied by acrylic acid or the like as a monomer, or the chemical influence (such as hydrolysis, etc.) when the polymer is modified by the carboxyl group.
[0064] The crosslinking monomer that can be used in the method of using the crosslinking monomer in the polymerization stage of the monomers is not particularly limited, and examples thereof include crosslinking vinyl compounds such as glycidyl methacrylate, N-methylol acrylamide, triallyl isocyanurate, triallyl cyanurate, divinylbenzene, hydroxyethyl methacrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and methylenebisacrylamide. Among them, the crosslinking structure based on triallyl isocyanurate, triallyl cyanurate, divinylbenzene, and methylenebisacrylamide is chemically stable when a crosslinked polymer containing these monomers is subjected to hydrolysis for the introduction of carboxyl groups, and is therefore preferred.
[0065] In addition, as a method for utilizing post-crosslinking, there is no particular limitation, for example, the following post-crosslinking method can be cited: the nitrile group contained in the nitrile polymer composed of a vinyl monomer with a nitrile group of more than 50% by weight is reacted with a hydrazine compound or formaldehyde. Wherein, the crosslinked structure introduced by the hydrazine compound is very stable to acid and alkali, and since the crosslinked structure formed is hydrophilic, it can help to improve hygroscopicity, and from the point of view of being able to introduce a firm crosslinking that can maintain the porous form of the polymer, the crosslinked structure introduced by the hydrazine compound is extremely excellent. It should be noted that, about the crosslinked structure obtained by the reaction, although its details have not yet been determined, it is presumed to be based on a triazole ring or a tetrazole ring structure.
[0066] The vinyl monomer having a nitrile group mentioned here is not particularly limited as long as it has a nitrile group, and specifically includes acrylonitrile, methacrylonitrile, ethacrylonitrile, α-chloroacrylonitrile, α-fluoroacrylonitrile, vinylidene cyanide, etc. Among them, acrylonitrile is most preferred because it has an advantage in cost and a large amount of nitrile groups per unit weight.
[0067] As a method for introducing crosslinking by reacting with a hydrazine compound, there is no particular limitation as long as the target crosslinking structure can be obtained, and the concentration of acrylonitrile polymer and hydrazine compound during the reaction, the solvent used, the reaction time, the reaction temperature, etc. can be appropriately selected as needed. Among them, with respect to the reaction temperature, if the temperature is too low, the reaction rate will slow down, and the reaction time will become too long. In addition, if the temperature is too high, sometimes the raw material acrylonitrile polymer will be plasticized, and the problem of the morphology of the polymer being destroyed will occur. Therefore, the preferred reaction temperature is 50 to 150 ° C, and more preferably 80 ° C to 120 ° C. In addition, there is no particular limitation on the part of the acrylonitrile polymer reacted with the hydrazine compound, and it can be appropriately selected according to its use and the morphology of the polymer. Specifically, it can be appropriately selected to react only on the surface of the polymer, or to allow the reaction to proceed throughout the whole until the core, to limit a specific part to react, etc. The hydrazine compounds used herein include hydrazine salts such as hydrazine hydrate, hydrazine sulfate, hydrazine hydrochloride, hydrazine nitrate, hydrazine bromate, and hydrazine carbonate, and hydrazine analogs such as ethylenediamine, guanidine sulfate, guanidine hydrochloride, guanidine nitrate, guanidine phosphate, and melamine.
[0068] The adsorbent particles having a cross-linked structure used in the present invention can be produced as described above, but commercially available products can also be used. Examples of the adsorbent particles having a cross-linked structure include "Ecopot (registered trademark) HU-750P" manufactured by Toyobo Co., Ltd.
[0069] In addition, after the adsorbent particles are produced as described above, it is also suitable to further impart a basic polymer such as polyethyleneimine to the surface thereof. By doing so, when a polyurethane-modified epoxy resin is used as a binder described later, the adhesion between the adsorbent particles and the binder will increase, and the strength of the adsorbent layer can be improved. As adsorbent particles imparted with a basic polymer, functional microparticles disclosed in International Publication No. 2014 / 188908 can be cited.
[0070] (3-2) Binder
[0071] The aforementioned binder is composed of an epoxy resin, a polyamine and a reactive diluent having two or more epoxy groups. First, the role of the epoxy resin is to load the adsorbent particles on the substrate, wherein polyurethane-modified epoxy resins, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, and chelate-modified epoxy resins are preferred, and polyurethane-modified bisphenol A-type epoxy resins and polyurethane-modified bisphenol F-type epoxy resins are more preferred. These resins can also be mixed and used. Specifically, ADEKA RESIN (registered trademark) EPU-11F (polyurethane-modified bisphenol A-type epoxy resin) and EPU-1001 (polyurethane-modified bisphenol F-type epoxy resin) made by ADEKA Co., Ltd. can be cited.
[0072] Secondly, the polyamine functions as a curing agent, and by crosslinking the aforementioned resin, the strength of the adsorbent layer can be increased, and cracking can be suppressed. As such polyamines, polyallylamine, polyethyleneimine, polydimethyldiallylamine chloride, xylene diamine, isophorone diamine, etc. can be cited. Only one polyamine can be used, or a combination of multiple polyamines can be used. In addition, the polyamine can also be a commercially available product, for example, jER CURE (registered trademark) LV11 manufactured by Mitsubishi Chemical Corporation, Daitocurar (registered trademark) D6293 manufactured by Daito Sangyo Co., Ltd., etc. can be cited.
[0073] The content of the polyamine in the binder is not particularly limited and may be appropriately selected according to the epoxy equivalent and content of the epoxy resin. When a commercially available polyamine is used, the blending amount specified by the manufacturer may be appropriately adopted.
[0074] The reactive diluent having two or more epoxy groups can suppress the decrease in the concentration of epoxy groups in the coating liquid containing the aforementioned adhesive component, while reducing the viscosity of the aforementioned coating liquid, thereby preventing thick coating and unevenness when applied to the substrate, and can also form a cross-linked structure in the aforementioned adhesive to improve its strength.
[0075] The viscosity of the reactive diluent at 25°C has no particular lower limit, but the lower the viscosity, the better. The upper limit is preferably 500 mPa·s, more preferably 400 mPa·s. If the viscosity is higher than 500 mPa·s, the viscosity of the coating liquid may not be sufficiently reduced.
[0076] In addition, there is no particular lower limit on the molecular weight of the reactive diluent, and there will be no problem as long as the molecular weight of ethylene glycol diglycidyl ether, which has the simplest structure among commonly used reactive diluents, is 174 or more. In addition, the upper limit is preferably 500, and more preferably 300. Generally, there is a positive correlation between molecular weight and viscosity, so if the molecular weight of the reactive diluent is higher than 500, the viscosity will also become high, and there is a concern that the viscosity of the coating liquid cannot be sufficiently reduced.
[0077] The epoxy equivalent of the reactive diluent is preferably 50 g / eq, more preferably 70 g / eq as a lower limit. If the epoxy equivalent is less than 50 g / eq, the cross-linked structure may be too dense, and there is a concern that it may become hard and brittle. In addition, the upper limit is preferably 200 g / eq, and more preferably 150 g / eq. If the epoxy equivalent is higher than 200 g / eq, the epoxy group decreases relative to the amount of the reactive diluent added to the coating solution, and there is a concern that the effect of increasing the strength of the adhesive by cross-linking described above may not be fully obtained.
[0078] Examples of such reactive diluents include ethylene glycol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, etc. Commercially available products may also be used, and examples thereof include Denacol (registered trademark) EX810 manufactured by ADEKA Co., Ltd., ADEKA GLYCIROL (registered trademark) ED523T, and Denacol (registered trademark) EX313 manufactured by Nagase ChemteX Corporation.
[0079] The content of the reactive diluent in the adhesive is preferably 100 parts by weight or less, and more preferably 70 parts by weight or less, based on 100 parts by weight of the epoxy resin.
[0080] The content of the aforementioned binder, as a lower limit, is 30 parts by weight, preferably 50 parts by weight, and more preferably 60 parts by weight relative to 100 parts by weight of the adsorbent particles. If the content of the aforementioned binder is less than 30 parts by weight relative to 100 parts by weight of the adsorbent particles, the adhesion between the corrosion-resistant film and the adsorbent and between the adsorbents will be reduced, resulting in easy peeling. In addition, as an upper limit, it is 110 parts by weight, preferably 100 parts by weight, relative to 100 parts by weight of the adsorbent particles. If the content of the aforementioned binder exceeds 110 parts by weight relative to 100 parts by weight of the adsorbent particles, the binder excessively covers the surface of the adsorbent particles, making it difficult to fully exert the function of the adsorbent.
[0081] The lower limit of the amount of adsorbent layer loaded on the single surface of the substrate in the present invention is 20 g / m 2 , preferably 30g / m 2 If the adsorbent layer loading is less than 20 g / m 2 , it is difficult to fully exert the moisture absorption capacity. In addition, as the upper limit, it is 80g / m 2 , preferably 70g / m 2 If the adsorbent layer loading is higher than 80 g / m 2 , the adsorbent layer will easily peel off from the substrate and the durability will be reduced.
[0082] In addition, the moisture absorption of the adsorbent layer is preferably 10 g / m2 as the lower limit in the measurement method described below. 2 , more preferably 15g / m 2 If the moisture absorption amount is below the lower limit, sufficient moisture absorption performance may not be obtained.
[0083] The heat transfer fins in the present invention are obtained by, for example, coating a coating liquid on the surface of a metal plate having the above-mentioned corrosion-resistant film containing epoxy resin and excellent thermal conductivity and baking the coating liquid, wherein the coating liquid contains adsorbent particles formed of organic polymers having carboxyl groups, polyamines, reactive diluents having two or more epoxy groups, epoxy resins, and solvents. At this time, the coating method includes the following: a method of immersing a substrate in the coating liquid and then draining it by centrifugal separation, squeezing rollers, etc.; a method of applying the coating liquid to a substrate using a scraper, a scraper, etc.; or a method of spraying the coating liquid onto a substrate; etc.
[0084] In addition to the above-mentioned components, other components such as antibacterial agents, preservatives, etc. can be added to the aforementioned coating liquid as needed. In addition, if an organic solvent is used as the solvent of the aforementioned coating liquid, it is preferred because it can suppress the volume change of the adsorbent particles accompanying water swelling. Among them, when ketones are used as solvents, during baking and reaction, a part of the ketones will reversibly generate ketimines with the polyamines, thereby suppressing the cross-linking reaction rate of the polyamines and the epoxy resin, and therefore, the unevenness of the reaction can also be reduced, which is more preferred. As such ketones, for example, acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, diethyl ketone, benzyl methyl ketone, diisopropyl ketone, cyclopentanone, cyclohexanone, etc. can be cited.
[0085] When preparing the coating liquid, it is desirable to first prepare a solution containing an epoxy resin, a reactive diluent having two or more epoxy groups, an organic solvent, and adsorbent particles formed of an organic polymer having a carboxyl group, and then add the polyamine to the solution. If the polyamine is added before adding other components other than the epoxy resin, the epoxy resin will be cured at this point, which may cause trouble in the subsequent steps of preparing the coating liquid and applying the coating.
[0086] The heat transfer fins provided with an adsorbent layer used in the present invention described above are not prone to cracking or peeling of the adsorbent layer due to the high strength and adhesion of the adsorbent layer, and can withstand mechanical processing. Therefore, even if the heat transfer fins are subjected to a flanging process (a hole is punched and a rise (flange) is applied around the hole), a heat transfer tube is inserted, and the adsorption heat exchange component is assembled (hereinafter referred to as a pre-coating method), an adsorption heat exchange component with no cracking or peeling of the adsorbent layer can be obtained. That is, there is no need to adopt a method of forming an adsorbent layer by impregnating a pre-assembled component with a liquid containing an adsorbent (hereinafter referred to as an impregnation coating method) as in the past.
[0087] The adsorption heat exchange component of the present invention is composed of the aforementioned multiple heat transfer fins and heat transfer tubes penetrating the heat transfer fins, and there is no portion between adjacent heat transfer fins where the adsorbent layers on the heat transfer fins come into contact and block the gap.
[0088] The aforementioned adsorption heat exchange component has, for example, Figure 1 The shape shown is manufactured by pre-coating using the heat transfer fin provided with the adsorbent layer. Specifically, it can be manufactured through the following steps: a step of providing an adsorbent layer on the surface of the heat transfer fin provided with a corrosion-resistant film, wherein the adsorbent layer contains adsorbent particles formed by an organic polymer having a carboxyl group and a binder formed by polyamine, a reactive diluent having two or more epoxy groups and an epoxy resin; a step of punching the heat transfer fin provided with the above-mentioned adsorbent layer to open holes; and a step of inserting a heat transfer tube into the above-mentioned multiple holes. That is, after obtaining the heat transfer fin provided with the adsorbent layer, it can be manufactured in the same method as the conventional method of manufacturing a heat exchange component. It should be noted that as the material of the heat transfer tube, the same material as the above-mentioned metal plate with excellent thermal conductivity can be used.
[0089] In the pre-coating method, there will be no poor drainage of the adsorbent-containing liquid as in the impregnation coating method. Therefore, even if the interval between the heat transfer fins is reduced, there will be no problem of blockage between the heat transfer fins. Therefore, in the adsorption heat exchange component of the present invention, the interval between adjacent heat transfer fins can preferably be set to less than 2 mm, more preferably less than 1.5 mm, and further preferably less than 1.3 mm. On the other hand, from the perspective of allowing air circulation, the lower limit of the interval between adjacent heat transfer fins is preferably greater than 0.3 mm. It should be noted that the "interval between adjacent heat transfer fins" in the present invention refers to the distance between the substrates constituting the heat transfer fins, which is controlled by the flange height in the flange processing described later.
[0090] As described above, the adsorption heat exchange assembly of the present invention can reduce the interval between adjacent heat transfer fins, can expand the adsorbent layer area per unit volume, and thus can increase the amount of adsorbent per unit volume. In particular, even if the amount of adsorbent per unit volume is increased than before, the blockage between the heat transfer fins caused by the adsorbent can still be avoided, which is a significant advantage of the present invention.
[0091] The adsorbent amount per unit volume is preferably 20 to 60 kg / m 3 , more preferably 22 to 55 kg / m 3 If it exceeds 60kg / m 3 If the adsorbent layer is too thick, the pores between the heat transfer fins will become narrower, and the pressure loss when the air passes through may be too large. 3 , there is a concern that sufficient moisture absorption performance may not be obtained.
[0092] In summary, the adsorption heat exchange component of the present invention has a narrower space between the heat transfer fins and a larger amount of adsorbent per unit volume of the component, so the latent heat treatment efficiency is better than before. The adsorption heat exchange component of the present invention can construct a compact and efficient dehumidification system, so it can be applied to dehumidification systems such as latent heat and sensible heat separation air conditioners and frost-free refrigeration equipment that can suppress frost generation during low-temperature operation.
[0093] In addition, by integrating the adsorption heat exchange component into a heat cycle, an energy-saving and stable ventilation and air-conditioning system can be provided.
[0094] Example
[0095] The present invention is specifically described below with reference to the following examples, but the present invention is not limited to the following examples. It should be noted that the parts and percentages in the examples are expressed by weight unless otherwise specified. First, the evaluation method of each characteristic is described.
[0096] [Total carboxyl group content]
[0097] About 1 g of the adsorbent sample was dried at 105°C for 16 hours and the weight (X [g]) was measured. After adding 200 ml of water, 1N hydrochloric acid aqueous solution was added while heating to 50°C to adjust the pH to 2, thereby converting all the carboxyl groups contained in the sample into H-type carboxyl groups. Then, a titration curve was obtained using 0.1N sodium hydroxide aqueous solution according to a conventional method. From the titration curve, the amount of sodium hydroxide aqueous solution consumed by the H-type carboxyl groups (V [ml]) was obtained, and the total amount of carboxyl groups contained in the sample was calculated according to the following formula.
[0098] [Formula] Total carboxyl content [mmol / g] = 0.1V / X
[0099] [Neutralization degree]
[0100] In the case where the pH is not adjusted to 2 by adding 1N hydrochloric acid aqueous solution in the above total carboxyl group amount measurement operation, a titration curve is similarly obtained to determine the amount of H-type carboxyl groups contained in the sample. From these results, the degree of neutralization is calculated according to the following formula.
[0101] [Formula] Neutralization degree = {(total carboxyl group content) - (H-type carboxyl group content)} / (total carboxyl group content)
[0102] [Weight average particle size]
[0103] The average particle size was determined from the particle size distribution expressed on a volume basis by using a laser diffraction particle size distribution analyzer "SALD-200V" manufactured by Shimadzu Corporation and measuring water as a dispersion medium.
[0104] [Swelling ratio]
[0105] After drying 20 g of adsorbent particles at 120°C for 2 hours, place them in a 100 mL measuring cylinder and read the volume (A [mL]). After that, add ion exchange water until the 100 mL mark on the test tube is reached, let stand for 2 hours, and read the volume of the sample again (B [mL]). From these results, the swelling ratio of the adsorbent particles is calculated according to the following formula.
[0106] [Formula] Swelling ratio [times] = B / A
[0107] [Method for measuring viscosity of reactive diluent]
[0108] The viscosity at 25° C. was measured using a viscometer (LVDV-II+ manufactured by Brookfield).
[0109] [Measurement method of epoxy equivalent]
[0110] The measurement was conducted in accordance with JIS K7236.
[0111] [Moisture absorption of the adsorbent layer on the heat transfer fins]
[0112] For the heat transfer fins (area A [m 2 ]), the weight after drying at 105°C for 16 hours (W0 [g]), and the weight after being placed at 20°C × 65% RH for 16 hours (W s [g]). From these results, the moisture absorption per unit area of the heat transfer fins was calculated according to the following formula.
[0113] [Formula] Moisture absorption per unit area of heat transfer fins [g / m 2 ]=(W s -W0) / A
[0114] [Ease of peeling]
[0115] The measurement was performed in accordance with Japanese Industrial Standard JIS-K5600-5-6.
[0116] Specifically, first, the adsorbent layer of the heat transfer fins prepared in the following examples was cut into a grid shape with a cutting knife, and 100 square pieces with a side length of 2 mm were formed on the adsorbent layer. Adhesive tape CELLOTAPE (registered trademark) CT-24S (width 24 mm) manufactured by NICHIBAN Co., Ltd. was attached to these square pieces. After that, the transparent tape was peeled off at an angle of 60° to the heat transfer fins, and the state of the square pieces remaining on the substrate was evaluated according to the following criteria.
[0117] (Benchmark)
[0118] 0: The cut edges are completely smooth and there is no peeling on all grids.
[0119] 1: There is a small peeling of the coating at the intersection of the cuts, but the affected area is not more than 5%.
[0120] 2: The coating peels off along the cut edges and / or at the intersections. The cross-cut area is significantly more than 5% but not more than 15% affected.
[0121] 3: The coating film peels off partially or completely along the cut edge, and / or peels off partially or completely in each part of the grid. The affected area is obviously more than 15% but not more than 35%.
[0122] 4: The coating peels off partially or completely along the cut edge, and / or multiple cross-cuts peel off partially or completely. The cross-cut area is significantly affected by more than 35% but not more than 65%.
[0123] 5: The degree of peeling exceeds that of category 4.
[0124] From the viewpoint of adhesion between the adsorbent layer and the substrate, the above evaluation is preferably 0 to 1.
[0125] [Film hardness]
[0126] The measurement was performed in accordance with Japanese Industrial Standard JIS-K5600-5-4.
[0127] Specifically, for the adsorbent layer of the heat transfer fin produced in the following embodiment, a pencil lead is pressed on it at an angle of 45 degrees and a load of 750g, and whether there are scratches is confirmed. The pencil lead hardness that is one level softer than the pencil lead hardness when the scratch is generated is taken as the pencil hardness.
[0128] From the viewpoint of scratch resistance, the pencil hardness of the adsorbent layer is preferably HB to 9H.
[0129] [Water resistance test]
[0130] The heat transfer fins prepared in the following examples were dried at 105°C for 16 hours (W0[g]), immersed in water for 5 minutes, and then dried with hot air at 75°C for 5 minutes. The process from immersion to drying was regarded as one cycle, and the above process was repeated 500 times. Here, the weight of the aluminum plate constituting the above heat transfer fins is denoted as w0[g], and the weight of the test piece after 500 cycles is denoted as W0[g]. 500 When [g], the residual rate of the coating film after 500 cycles was calculated according to the following formula.
[0131] Residual rate [%] = {(W 500 -w0) / (W0-w0)}×100
[0132] If the residual rate is 50% or more, it can be considered that the water resistance is sufficient for practical use.
[0133] [State of the adsorbent layer]
[0134] The state of the adsorbent layer on the heat transfer fins subjected to the burring process was visually evaluated according to the following criteria.
[0135] [Evaluation Criteria]
[0136] ◎: The average number of cracks / peeling sites around the hole per hole is 0 (no cracks / peeling)
[0137] ○: The average value of the number of cracks / peeling sites around the hole per hole is more than 0 and less than 1
[0138] △: The average number of cracks / peeling sites around the hole per hole is more than 1 and less than 2
[0139] ×: The average number of cracks or peeling sites around a hole is more than 2 per hole
[0140] [Adsorbent amount per unit volume]
[0141] The adsorbent amount per unit volume was calculated according to the following formula.
[0142] [Formula] Adsorbent dosage per unit volume [kg / m 3 ]
[0143] ={(area of one heat transfer fin×coating amount per single side×2)×(adsorbent ratio in coating amount)} / {area of one heat transfer fin×(thickness of substrate with corrosion resistant film+interval between adjacent heat transfer fins)}
[0144] = (coating amount per single side × 2 × adsorbent ratio in coating amount) / (thickness of substrate with corrosion-resistant film + interval between adjacent heat transfer fins)
[0145] [Hygroscopic performance of adsorption heat exchange components]
[0146] While 35°C salt water flows into the heat transfer tube of the adsorption heat exchange component, air with a temperature of 35°C and an absolute humidity of 3.47g / kg (relative humidity 10%) is supplied at a wind speed of 1m / s. After reaching a stable state, the circulation of the salt water is stopped, and the supplied air is switched to air with a temperature of 35°C and an absolute humidity of 21.44g / kg (relative humidity 60%), and the air is supplied at a wind speed of 1m / s. From the start of the air supply, the absolute humidity difference and air volume of the inlet and outlet air of the adsorption heat exchange component are continuously measured by sensors, and the moisture absorption is calculated based on these measured values, and the time-dependent changes in the cumulative moisture absorption are observed.
[0147] [Example 1]
[0148] 71 parts by weight of ADEKA RESIN (registered trademark) EPU-11F (epoxy equivalent: 280 g / eq), a polyurethane-modified bisphenol A epoxy resin manufactured by ADEKA Co., Ltd., is diluted with 29 parts by weight of Denacol (registered trademark) EX810 (epoxy equivalent: 113 g / eq, viscosity: 20 mPa·s, molecular weight: 174), an epoxy-based reactive diluent manufactured by Nagase ChemteX Corporation, and then methyl ethyl ketone (20 parts by weight) is added. Subsequently, 133.3 parts by weight of ICOPOPD (registered trademark) HU-750P (total carboxyl group content: 6.45 mmol / g, degree of neutralization: 80%, weight-average particle size: 30 μm, swelling ratio: 2.5 times), an organic polymer adsorbent particle manufactured by Toyobo Co., Ltd., is added and dispersed by stirring. 33.3 parts by weight of polyamine jER CURE (registered trademark) LV11 (amine value: 545 mgKOH / g) manufactured by Mitsubishi Chemical Corporation was added thereto to prepare a coating liquid.
[0149] The coating liquid was applied to an aluminum material DC301 (plate thickness 0.15 mm, 5 cm×8 cm) having a corrosion-resistant film containing epoxy resin manufactured by KATAGI ALUMINUM PRODUCTS LTD., such that the coating amount per single side after drying (i.e., the amount supported by the adsorbent layer) was 63.3 g / m 2 , and baked at 120°C for 60 minutes to obtain a heat transfer fin.
[0150] [Example 2]
[0151] In Example 1, as the epoxy resin, 61 parts by weight of ADEKA RESIN (registered trademark) EPU-1001 (epoxy equivalent: 220 g / eq) of a chelate-modified bisphenol F epoxy resin manufactured by ADEKA Corporation was used, and as the reactive diluent, 39 parts by weight of ADEKA GLYCIROL (registered trademark) ED523T (epoxy equivalent: 140 g / eq, viscosity: 15 mPa·s, molecular weight: 216) manufactured by ADEKA Corporation was used, and the coating amount per single side after the coating liquid was dried was 68.7 g / m 2 The heat transfer fin of Example 2 was obtained by the same operation as above except that the coating was performed in the manner of .
[0152] [Example 3]
[0153] In Example 1, 66 parts by weight of EPU-1001 was used as the epoxy resin, and 34 parts by weight of EX810 was used as the reactive diluent. The coating amount per single side after the coating liquid was dried was 55.7 g / m 2 The heat transfer fin of Example 3 was obtained by the same operation as above except that the coating was performed in the manner of .
[0154] [Example 4]
[0155] In Example 1, 66.7 parts by weight of EPU-11F was used as the epoxy resin, and 33.3 parts by weight of ED523T was used as the reactive diluent. The coating amount per single side after the coating liquid was dried was 61.3 g / m 2 The heat transfer fin of Example 4 was obtained by the same operation as above except that the coating was performed in the manner of .
[0156] [Example 5]
[0157] In Example 4, 25 parts by weight of LV11 was used as the polyamine, 66.5 parts by weight of HU-750P1 was used as the adsorbent particles, and 53.3 parts by weight of methyl ethyl ketone was used. The coating amount per single side after the coating liquid was dried was 63.9 g / m 2 The heat transfer fin of Example 5 was obtained by the same operation as above except that the coating was performed in the manner of .
[0158] [Example 6]
[0159] In Example 1, 50 parts by weight of a modified aliphatic polyamine, Daitocurar (registered trademark) D6293 (amine value: 262 mgKOH / g), manufactured by Daito Sangyo Co., Ltd., was used as a polyamine, 150 parts by weight of HU-750P (pH 8) (total carboxyl group content: 6.45 mmol / g, neutralization degree: 65%, weight average particle size: 30 μm, swelling ratio 2.0 times) was used as adsorbent particles, and 35.1 parts by weight of methyl ethyl ketone was used, so that the coating amount per single side after the coating liquid was dried was 50 g / m 2 The heat transfer fin of Example 6 was obtained in the same manner except that HU-750P (pH 8) was applied in the same manner. Here, HU-750P (pH 8) is obtained by dispersing HU-750P in ion exchange water to prepare a dispersion, adding dilute nitric acid so that the pH of the dispersion becomes 8, filtering, washing with water, and drying.
[0160] [Example 7]
[0161] In Example 1, 61 parts by weight of EPU-11F was used as the epoxy resin, 39 parts by weight of ED523T was used as the reactive diluent, 50 parts by weight of D6293 was used as the polyamine, 159.7 parts by weight of HU-750P was used as the adsorbent particles, and 53.9 parts by weight of methyl ethyl ketone was used, so that the coating amount per single side after the coating liquid was dried was 61 g / m 2 The heat transfer fin of Example 7 was obtained by the same operation as above except that the coating was performed in the manner of .
[0162] [Example 8]
[0163] In Example 1, as adsorbent particles, 133.3 parts by weight of HU-720SF (total carboxyl group content: 6.45 mmol / g, neutralization degree: 65%, weight average particle size: 4 μm, swelling ratio 2.5 times) manufactured by Exlan Industries, Ltd. of Japan was used, and the coating amount per single side after the coating liquid was dried was 55 g / m 2 The heat transfer fin of Example 8 was obtained by the same operation as above except that the coating was performed in the manner of .
[0164] [Example 9]
[0165] In Example 1, 60 parts by weight of bisphenol A epoxy resin JER (registered trademark) 801N (epoxy equivalent: 215 g / eq) manufactured by Mitsubishi Chemical Corporation was used as the epoxy resin, 40 parts by weight of Denacol (registered trademark) EX313 (epoxy equivalent: 141 g / eq, viscosity: 150 mPa·s, molecular weight: 205 and 236) manufactured by Nagase ChemteX Corporation, which is an epoxy reactive diluent formed of two compounds, was used as the reactive diluent, 57 parts by weight of D6293 was used as the polyamine, 150 parts by weight of HU-750P was used as the adsorbent particles, and 7 parts by weight of methyl ethyl ketone was used, so that the coating amount per single side after the coating liquid was dried was 80 g / m 2 The heat transfer fin of Example 9 was obtained by the same operation as above except that the coating was performed in the manner of .
[0166] [Example 10]
[0167] For Example 1, as adsorbent particles, organic polymer adsorbent particles (total carboxyl group content: 6.45 mmol / g, neutralization degree: 80%, weight average particle size: 30 μm, swelling ratio 2.5 times) endowed with alkaline polymer were manufactured using the method described in the Example of International Publication No. 2014 / 188908. The particles were used so that the coating amount per single side after the coating liquid was dried was 55.3 g / m 2The heat transfer fin of Example 10 was obtained by the same operation as above except that the coating was performed in the manner of .
[0168] [Comparative Example 1]
[0169] In Example 1, 50 parts by weight of D6293 was used as the polyamine, 150 parts by weight of HU-750P was used as the adsorbent particles, 16.8 parts by weight of methyl ethyl ketone was used, and JIS A1050, which is industrial pure aluminum, was used as the aluminum plate. The coating amount per single side after the coating liquid was dried was 108 g / m 2 The heat transfer fin of Comparative Example 1 was obtained in the same manner as above except that the coating was performed in the same manner as above.
[0170] [Comparative Example 2]
[0171] In Comparative Example 1, the coating amount per single side after the coating liquid was dried was 156 g / m 2 The heat transfer fin of Comparative Example 2 was obtained in the same manner as above except that the coating was performed in the same manner as above.
[0172] [Comparative Example 3]
[0173] In Example 1, 380.9 parts by weight of HU-750P and 50 parts by weight of methyl ethyl ketone were used as adsorbent particles, and the coating amount per single side after the coating liquid was dried was 100 g / m 2 The heat transfer fin of Comparative Example 3 was obtained in the same manner as above except that the coating was performed in the same manner as above.
[0174] [Comparative Example 4]
[0175] In Example 1, as polyamine, 50 parts by weight of D6293, 150 parts by weight of HU-750P (pH 4) (total carboxyl group content: 6.45 mmol / g, neutralization degree: 30%, weight average particle size: 30 μm, swelling ratio 1.0 times) and 35.1 parts by weight of methyl ethyl ketone were used, and the coating amount per single side after the coating liquid was dried was 50 g / m 2 The heat transfer fin of Comparative Example 4 was obtained in the same manner except that HU-750P (pH 4) was applied in the same manner. Here, HU-750P (pH 4) means that HU-750P was dispersed in ion exchange water to prepare a dispersion, dilute nitric acid was added until the pH of the dispersion reached 2, and then the dispersion was filtered to obtain a filtrate, and the filtrate was washed with ion exchange water until the pH reached 4, filtered, and dried.
[0176] [Comparative Example 5]
[0177] In Example 1, 133.3 parts by weight of HU-720SF was used as the adsorbent particles, and the coating amount per single side after the coating liquid was dried was 15 g / m 2The heat transfer fin of Comparative Example 5 was obtained in the same manner as above except that the coating was performed in the same manner as above.
[0178] [Comparative Example 6]
[0179] In Example 1, 90 parts by weight of HU-750P and 10 parts by weight of methyl ethyl ketone were used as adsorbent particles, and the coating amount per single side after the coating liquid was dried was 52 g / m 2 The heat transfer fin of Comparative Example 6 was obtained in the same manner as above except that the coating was performed in the same manner as above.
[0180] [Comparative Example 7]
[0181] In Example 1, 41 parts by weight of EPU-1001 was used as the epoxy resin, 59 parts by weight of ADEKA GLYCIROL (registered trademark) ED502 (epoxy equivalent: 320 g / eq, viscosity: 10 mPa·s, molecular weight: 242 and 256) manufactured by ADEKA Co., Ltd., which contains two compounds having one epoxy group, was used as the reactive diluent, 337 parts by weight of D629 was used as the polyamine, 150 parts by weight of HU-750P was used as the adsorbent particles, and 10 parts by weight of methyl ethyl ketone was used, so that the coating amount per single side after the coating liquid was dried was 57 g / m 2 The heat transfer fin of Comparative Example 7 was obtained in the same manner as above except that the coating was performed in the same manner as above.
[0182] [Comparative Example 8]
[0183] In Example 1, 100 parts by weight of EPU-11F was used as the epoxy resin, 36 parts by weight of D6293 was used as the polyamine, 150 parts by weight of HU-750P was used as the adsorbent particles, 10 parts by weight of methyl ethyl ketone was used, and no reactive diluent was used. The coating amount per single side after the coating liquid was dried was 58 g / m 2 The heat transfer fin of Comparative Example 8 was intended to be obtained in the same manner as above except that the coating was performed in the same manner. However, the adsorbent layer was not completely cured.
[0184] The above-mentioned evaluation test was carried out on the heat transfer fins of each example and comparative example, and the results are shown in Table 1.
[0185] [Table 1]
[0186]
[0187] “-” indicates no evaluation / measurement was performed
[0188] As shown in Table 1, the heat transfer fins described in the Examples all have excellent durability and moisture absorption and release, while the heat transfer fins described in the Comparative Examples are inferior in at least one of durability and / or moisture absorption.
[0189] [Example 11]
[0190] 71 parts by weight of ADEKA RESIN (registered trademark) EPU-11F (epoxy equivalent: 280 g / eq), a polyurethane-modified bisphenol A epoxy resin manufactured by ADEKA Co., Ltd., is diluted with 29 parts by weight of Denacol (registered trademark) EX810 (epoxy equivalent: 113 g / eq, viscosity: 20 mPa·s, molecular weight: 174), an epoxy-based reactive diluent manufactured by Nagase ChemteX Corporation, and then methyl ethyl ketone (20 parts by weight) is added. Subsequently, 133.3 parts by weight of ICOPOPD (registered trademark) HU-750P (total carboxyl group content: 6.45 mmol / g, degree of neutralization: 80%, weight-average particle size: 30 μm, swelling ratio: 2.5 times), an organic polymer adsorbent particle manufactured by Toyobo Co., Ltd., is added and dispersed by stirring. 33.3 parts by weight of polyamine jER CURE (registered trademark) LV11 (amine value: 545 mgKOH / g) manufactured by Mitsubishi Chemical Corporation was added thereto to prepare a coating liquid.
[0191] The coating liquid was applied on both sides of an aluminum fin material (thickness 0.1 mm, 255 mm × 45 mm) provided with a corrosion-resistant film containing epoxy resin after phosphate chromate treatment, so that the coating amount per single side after drying (i.e., the loading amount of the adsorbent layer) was 40 g / m 2 , and baked at 120°C for 60 minutes to obtain a heat transfer fin.
[0192] The obtained heat transfer fins were flanged with 20 circular holes of 9.88 mm in diameter so that the interval between the heat transfer fins when stacked was 1.5 mm. Next, 120 of the obtained heat transfer fins were stacked, and a copper heat transfer tube of 9.52 mm in outer diameter was inserted, and a heat transfer tube was prepared according to a known method. Figure 1 The adsorption heat exchange component shown.
[0193] [Example 12]
[0194] In Example 11, 61 parts by weight of ADEKA RESIN (registered trademark) EPU-1001 (epoxy equivalent: 220 g / eq), a chelate-modified bisphenol F epoxy resin manufactured by ADEKA Corporation, was used as the epoxy resin, and 39 parts by weight of ADEKA GLYCIROL (registered trademark) ED523T (epoxy equivalent: 140 g / eq, viscosity: 15 mPa·s, molecular weight: 216), manufactured by ADEKA Corporation, was used as the reactive diluent, so that the coating amount per single side after the coating liquid was dried was 41 g / m 2 The heat transfer fin and adsorption heat exchange component of Example 12 are obtained by coating in the same manner as above and otherwise performing the same operation.
[0195] [Example 13]
[0196] In Example 11, 66 parts by weight of EPU-1001 was used as the epoxy resin, and 34 parts by weight of EX810 was used as the reactive diluent, so that the coating amount per single side after the coating liquid was dried was 40 g / m 2 The heat transfer fin and adsorption heat exchange component of Example 13 are obtained by coating in the same manner as above and otherwise performing the coating.
[0197] [Example 14]
[0198] In Example 11, 66.7 parts by weight of EPU-11F was used as the epoxy resin, and 33.3 parts by weight of ED523T was used as the reactive diluent. The coating amount per single side after the coating liquid was dried was 39.5 g / m 2 The heat transfer fin and adsorption heat exchange component of Example 14 are obtained by coating in the same manner as above, except that the coating is performed in the same manner as above.
[0199] [Example 15]
[0200] In Example 14, 25 parts by weight of LV11 was used as the polyamine, 66.7 parts by weight of HU-750P1 was used as the adsorbent particles, and 50 parts by weight of methyl ethyl ketone was used, so that the coating amount per single side after the coating liquid was dried was 45 g / m 2 The heat transfer fins and adsorption heat exchange components of Example 15 are obtained by coating in the same manner as above and otherwise performing the same operation.
[0201] [Example 16]
[0202] In Example 15, 166.5 parts by weight of HU-750P and 53.3 parts by weight of methyl ethyl ketone were used as adsorbent particles, and the coating amount per single side after the coating liquid was dried was 39.5 g / m 2The heat transfer fin and adsorption heat exchange component of Example 16 are obtained by coating in the same manner as above and otherwise performing the coating.
[0203] [Example 17]
[0204] In Example 16, the coating amount per single side after the coating liquid was dried was 50.4 g / m 2 The heat transfer fins and adsorption heat exchange components of Example 17 are obtained by coating in the same manner as above and otherwise performing the coating.
[0205] [Example 18]
[0206] In Example 11, 50 parts by weight of a modified aliphatic polyamine, Daitocurar (registered trademark) D6293 (amine value: 262 mgKOH / g), manufactured by Daito Sangyo Co., Ltd., was used as the polyamine, 150 parts by weight of HU-750P (pH 8) (total carboxyl group content: 6.45 mmol / g, neutralization degree: 65%, weight average particle size: 30 μm, swelling ratio 2.0 times) was used as the adsorbent particles, and 35.1 parts by weight of methyl ethyl ketone was used, so that the coating amount per single side after the coating liquid was dried was 40.5 g / m 2 The heat transfer fin and adsorption heat exchange component of Example 18 were obtained in the same manner except that the coating was performed in the same manner. Here, HU-750P (pH 8) refers to a dispersion prepared by dispersing HU-750P in ion exchange water, adding dilute nitric acid so that the pH of the dispersion becomes 8, filtering, washing with water, and drying.
[0207] [Example 19]
[0208] In Example 11, 61 parts by weight of EPU-11F was used as the epoxy resin, 39 parts by weight of ED523T was used as the reactive diluent, 50 parts by weight of D6293 was used as the polyamine, 159.7 parts by weight of HU-750P was used as the adsorbent particles, and 53.9 parts by weight of methyl ethyl ketone was used, so that the coating amount per single side after the coating liquid was dried was 40.6 g / m 2 The heat transfer fins and adsorption heat exchange components of Example 19 are obtained by coating in the same manner as above and otherwise performing the coating.
[0209] [Example 20]
[0210] In Example 11, 133.3 parts by weight of HU-720SF (total carboxyl group content: 6.45 mmol / g, neutralization degree: 65%, weight average particle size: 4 μm, swelling ratio 2.5 times) produced by Exlan Industries, Ltd. of Japan was used as adsorbent particles, and the coating amount per single side after the coating liquid was dried was 39.8 g / m 2The coating is carried out in the same manner as above, and the heat transfer fins and adsorption heat exchange components of Example 20 are obtained by the same operation except that the coating is carried out in the same manner as above.
[0211] [Example 21]
[0212] In Example 11, the flange processing was performed so that the interval between the heat transfer fins when stacked was 1.2 mm, and the coating amount per single side after the coating liquid dried was 40.6 g / m 2 The coating is carried out in the same manner as above, and the heat transfer fins and adsorption heat exchange components of Example 21 are obtained by the same operation except that the coating is carried out in the same manner as above.
[0213] [Example 22]
[0214] In Example 11, as the organic polymer adsorbent particles, the organic polymer adsorbent particles with alkaline polymer disclosed in Example 1 of International Publication No. 2014 / 188908 (total carboxyl group content: 6.6 mmol / g, neutralization degree: 94%, weight average particle size: 40 μm, swelling ratio 2.3 times) were used instead of HU-750P, and the coating amount per single side after the coating liquid was dried was 45 g / m 2 The heat transfer fin and adsorption heat exchange component of Example 22 were obtained in the same manner except that the coating was performed in the same manner. It should be noted that the organic polymer adsorbent particles endowed with alkaline polymers were produced as follows.
[0215] Add 700 parts by weight of water to a reaction tank with a volume of 2L, and then add a mixture of 210 parts by weight of acrylonitrile and 90 parts by weight of divinylbenzene. While stirring the reaction tank, add 3 parts by weight of ammonium persulfate (polymerization initiator) and dissolve it. After that, heat the reaction tank to 70°C and react them for 3 hours. After the reaction is completed, cool to about 20°C while continuing to stir to obtain cross-linked acrylonitrile polymer particles with an average particle size of 40μm. Next, add 800g of water, 100g of NaOH and 100g of the cross-linked acrylonitrile polymer particles to a reaction tank with a volume of 2L, and perform a hydrolysis reaction at 90°C for 60 hours to obtain salt-containing carboxyl particles. Furthermore, 900 g of water and 100 g of the salt-type carboxyl-containing particles were added to a reaction tank with a volume of 2 L, and 0.5 g of polyethyleneimine (average molecular weight 70,000) was added while stirring. The mixture was reacted at 50°C for 30 minutes, and then washed and dried to obtain organic polymer adsorbent particles endowed with alkaline polymers.
[0216] [Comparative Example 9]
[0217] In Example 12, 50 parts by weight of D6293 was used as the polyamine, 150 parts by weight of HU-750P was used as the adsorbent particles, 16.8 parts by weight of methyl ethyl ketone was used, and JIS A1050, which is industrial pure aluminum, was used as the aluminum plate. The coating amount per single side after the coating liquid was dried was 40 g / m 2 The heat transfer fin and adsorption heat exchange component of Comparative Example 9 were obtained by the same operation except that the coating was performed in the same manner.
[0218] [Comparative Example 10]
[0219] In Example 12, 533.2 parts by weight of HU-750P and 70 parts by weight of methyl ethyl ketone were used as the adsorbent particles, and the coating amount per single side after the coating liquid was dried was 40.6 g / m 2 The heat transfer fin and adsorption heat exchange component of Comparative Example 10 were obtained by the same operation except that the coating was performed in the same manner.
[0220] [Comparative Example 11]
[0221] In Example 12, 90 parts by weight of HU-750P and 10 parts by weight of methyl ethyl ketone were used as adsorbent particles, and the coating amount per single side after the coating liquid was dried was 39.7 g / m 2 The heat transfer fin and adsorption heat exchange component of Comparative Example 11 were obtained by the same operation except that the coating was performed in the same manner.
[0222] [Comparative Example 12]
[0223] For the heat transfer fins obtained on the aluminum fin material (plate thickness 0.1mm, width 110mm, length 360mm) provided with a corrosion-resistant film containing epoxy resin after phosphate chromate treatment, 20 circular holes with a diameter of 9.88mm were flanged in such a way that the interval between the heat transfer fins when stacked was 1.5mm. Then, 120 sheets of the obtained heat transfer fins were stacked, and a copper heat transfer tube with an outer diameter of 9.52mm was inserted, and a heat exchange component was made according to a known method. For the above heat exchange component, the immersion in the coating liquid prepared in Example 1, the removal and the draining by blowing with compressed air were repeated 5 times, and then baked at 120°C for 60 minutes to obtain the adsorption heat exchange component of Comparative Example 12.
[0224] The heat transfer fins of each embodiment and comparative example were subjected to the aforementioned evaluation test, and the results are shown in Table 1. Figure 2 The temporal changes in the moisture absorption of the adsorption heat exchange components of Examples 11, 21 and Comparative Example 11 are shown in FIG.
[0225] [Table 2]
[0226]
[0227] “-” indicates no evaluation / measurement was performed
[0228] As shown in Table 2, the heat transfer fins described in each embodiment are not easy to peel off while maintaining the hygroscopicity of the adsorbent layer, and almost no cracks will occur during the flanging process. In addition, due to this property, in the adsorption heat exchange component of the present invention using the above-mentioned heat transfer fins, a heat transfer fin spacing of less than 2 mm, which is narrower than before, can be achieved without blocking, and the adsorbent amount per unit volume can be increased, such as Figure 2 As shown, when the temperature, humidity, amount, and other conditions of the air are kept the same, more moisture can be removed from the air.
Claims
1. A heat transfer fin, characterized in that: have: A corrosion-resistant film provided on a surface of a metal plate having excellent thermal conductivity and containing an epoxy resin; and An adsorbent layer comprising adsorbent particles formed of an organic polymer having a carboxyl group and a binder formed of a polyamine, a reactive diluent having two or more epoxy groups, and an epoxy resin; The organic polymer has a carboxyl content of 3 to 10 mmol / g and a neutralization degree of 60 to 100%. The binder is used in an amount of 30 to 110 parts by weight relative to 100 parts by weight of the adsorbent particles, and the adsorbent particles and the binder are used in an amount of 20 to 80 g / m 2 An amount of is loaded on a single surface of the metal plate surface.
2. The heat transfer fin according to claim 1, characterized in that: The reactive diluent has a viscosity at 25° C. of 500 mPa·s or less.
3. The heat transfer fin according to claim 1, characterized in that: The epoxy equivalent of the reactive diluent is 50 to 200 g / eq.
4. The heat transfer fin according to claim 1, characterized in that: The weight average particle size of the adsorbent particles is 3 to 100 μm.
5. The heat transfer fin according to claim 1, characterized in that: The adsorbent particles have a swelling ratio in water of 5 times or less.
6. A method for manufacturing a heat transfer fin according to any one of claims 1 to 5, characterized in that: Including the following processes: A coating liquid containing adsorbent particles formed of organic polymers having carboxyl groups, polyamine, a reactive diluent having two or more epoxy groups, epoxy resin and an organic solvent is applied to the surface of a metal plate to which a corrosion-resistant film containing epoxy resin is applied and baked.
7. The method for manufacturing a heat transfer fin according to claim 6, characterized in that: Ketone was used as the organic solvent.
8. The method for manufacturing a heat transfer fin according to claim 6, characterized in that: Including the following processes: The coating liquid is prepared by adding a polyamine to a solution containing an epoxy resin, a reactive diluent having two or more epoxy groups, an organic solvent, and adsorbent particles formed of an organic polymer having a carboxyl group.
9. An adsorption heat exchange component, characterized in that: It is composed of a plurality of heat transfer fins provided with an adsorbent layer and a heat transfer tube penetrating the plurality of heat transfer fins. The plurality of heat transfer fins are the heat transfer fins according to claim 1, and there is no blocking portion caused by the adsorbent layer between adjacent heat transfer fins.
10. The adsorption heat exchange component according to claim 9, characterized in that: The interval between adjacent heat transfer fins is less than 2 mm.
11. The adsorption heat exchange component according to claim 9, characterized in that: The adsorbent dosage per unit volume is 20~60kg / m 3 .
12. A method for manufacturing an adsorption heat exchange component according to any one of claims 9 to 11, characterized in that: Including the following processes: The step of providing an adsorbent layer on the surface of the heat transfer fin provided with the corrosion-resistant film, wherein the adsorbent layer contains adsorbent particles formed of an organic polymer having a carboxyl group in the molecule and a binder formed of a polyamine, a reactive diluent having two or more epoxy groups and an epoxy resin; A step of punching holes in the heat transfer fins provided with the adsorbent layer to form holes; as well as The step of inserting a heat transfer tube into the plurality of holes.
13. A dehumidification system, using the adsorption heat exchange component according to any one of claims 9 to 11.
14. A ventilation and air-conditioning system using the adsorption heat exchange component according to any one of claims 9 to 11.
Citation Information
Patent Citations
Adsorption type reactor module
JP1994002984A
Sorption type heat exchange module, and its manufacturing method
JP2006200850A
Heat transfer fin, and heat exchanger
JP2012077987A
Functional microparticles and resin product containing same
WO2014188908A1
Cited By
Multi-mode double-channel heat exchange system, heat exchanger and control method
CN121898174A